(untitled) (Journal of the College of Basic Education, 2026)
This research deals with an in-depth analytical study of the military tactics adopted by Muslim leaders during the Islamic conquest of Andalusia in 92 AH، focusing on the strategic and practical dimensions that contributed to achieving this impressive military success. The research sheds light on the meticulous planning that preceded the crossing operation، which included gathering accurate intelligence information about the situation in the Iberian Peninsula through contacts with local allies such as Julian، the ruler of Ceuta، in addition to the reconnaissance campaigns led by Tariq ibn Malik، which paved the way for understanding the nature of the terrain and the enemy. The research also highlights the tactical prowess of the commander Tariq ibn Ziyad in managing battles، especially in the decisive Battle of Wadi Lakka، where his ability to exploit the terrain and apply the principles of surprise، maneuver، and warfare of attrition was demonstrated by defeating the Gothic army، which was superior in equipment and personnel. The analysis does not neglect the psychological and leadership aspects that formed a fundamental pillar of success، represented by the inspiring sermon of Tariq ibn Ziyad، which motivated the soldiers to persevere، and the wise policy in dealing with the local population، which ensured the long-term stability of the Islamic state in Andalusia. Through this comprehensive analysis، the research presents a comprehensive view of the tactical factors that transformed a bold military campaign into an exceptional cultural achievement whose influence extended across the centuries.